2020
DOI: 10.3758/s13421-020-01091-9
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of prospective memory intentions: Examining the role of the stimulus–response link

Abstract: Successful prospective remembering involves formation of a stimulus (e.g., bottle of medication and/or place where the bottle is kept)-response (e.g., taking a medication) link. We investigated the role of this link in the deactivation of no-longer-relevant prospective memory intentions, as evidenced by commission error risk. Experiment 1a contrasted two hypotheses of intention deactivation (degree of fulfillment and response frequency) by holding constant the degree of intention fulfillment (e.g., participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Such strategies might be expected to boost performance in light of accumulating evidence for a consistent impact even of merely instructed mapping rules (e.g., Braem et al, 2019 ; Cohen-Kdoshay & Meiran, 2009 ; Kunde et al, 2003 ; Meiran et al, 2015 ; Pfeuffer et al, 2017 ; Wenke et al, 2007 ), which is possibly mediated by the formation of efficient action triggers ( Kiesel et al, 2007 ) or implementation intentions (“if S rel , then R cor ”; Gollwitzer, 1999 ). This account would thus assume that previous evidence for goal-based binding mirrors covert strengthening of a mapping rule rather than actual binding (for a related discussion in the literature on prospective memory, see Streeper & Bugg, 2021 ).…”
mentioning
confidence: 99%
“…Such strategies might be expected to boost performance in light of accumulating evidence for a consistent impact even of merely instructed mapping rules (e.g., Braem et al, 2019 ; Cohen-Kdoshay & Meiran, 2009 ; Kunde et al, 2003 ; Meiran et al, 2015 ; Pfeuffer et al, 2017 ; Wenke et al, 2007 ), which is possibly mediated by the formation of efficient action triggers ( Kiesel et al, 2007 ) or implementation intentions (“if S rel , then R cor ”; Gollwitzer, 1999 ). This account would thus assume that previous evidence for goal-based binding mirrors covert strengthening of a mapping rule rather than actual binding (for a related discussion in the literature on prospective memory, see Streeper & Bugg, 2021 ).…”
mentioning
confidence: 99%
“…More recently, it has been described how binding of event files can lead to changes in episodic memory traces, which provides a link between event file coding and declarative memories (Frings et al, 2020). A similar approach was taken in case of prospective memories, that is, when someone has to remember the intention to act in the future (Streeper & Bugg, 2020). While these accounts are paramount in understanding S‐R associations as building blocks of declarative memories, it is important to consider that the most common task to investigate event file coding (Colzato et al, 2006) is one resembling procedural rather than declarative memory paradigms (Figure 2).…”
Section: Procedural Memory Formation and Event File Codingmentioning
confidence: 99%
“…Research on commission errors, or whether people respond to targets that are displayed after the prospective memory task has ended, has found that the number of targets encountered in the task predicts the rate of commission errors. Commission errors are higher when fewer of the targets are presented in the prospective memory task (Bugg & Scullin, 2013 ; Streeper & Bugg, 2021 ).…”
Section: Introductionmentioning
confidence: 99%